What is the most suitable hypoosmotic swelling test to assess functional integrity of cryopreserved equine sperm? - Snoeck, Paola Pereira das Neves; de Melo, Maria Isabel Vaz; Alves, Sidney Gonçalves Gonzalez; Bittencourt, Rodrigo Freitas; Filho, Antônio de Lisboa Ribeiro; Chalhoub, Marcos; Henry, Marc (Brazilian Journal of Veterinary Medicine, 2014)
ABSTRACT. Snoeck P.P.N., Melo M.I.V., Alves S.G.G., Bittencourt R.F., Ribeiro Filho A.L., Chalhoub M. & Henry M. [What is the most suitable hypoosmotic swelling test to assess functional integrity of cryopreserved equine sperm?] Qual é o teste hiposmótico mais indicado para avaliar a integridade funcional de espermatozoides equino criopreservados? Revista Brasileira de Medicina Veterinária, 36(4):355-361, 2014. Departamento de Ciências Agrárias e Ambientais, Universidade Estadual de Santa Cruz, Rodovia Jorge Amado, Km 16, Salobrinho, Ilhéus, BA 45662-000, Brasil. E-mail: paolasnoeck@uesc.br The aim of this work was to standardize the most efficient hypoosmotic swelling test (HOST) to determine the percentage of functional integrity of cryopreserved equine sperm by testing protocols with different solutes and distilled water, different incubation times in water bath, osmolarities, dilution rates and with or without formol-saline fixation. In experiment 1 the sucrose, fructose, sodium chloride and sodium citrate solutions with 50 and 100 mOsmol/L and the distilled water were tested in the dilutions rate of 1:10 and 1:20, incubated in water bath for 10 and 15 minutes. The types of hypoosmotic reaction were evaluated in phase contrast microscopy. There were no differences (P≥0.05) between the incubation times, osmolarities of solutions, and dilution rates of the semen with distilled water. The fructose solution was more efficient to determine the percentage of reactive sperm (P≤0.05) than the sodium chloride and sodium citrate solutions, but was similar to sucrose and distilled water (P≥0.05). The test with distilled water identified the higher percentage of reactive sperm with strongly coiled tails compared to the tests with hypoosmotic solutions with 50 and 100mOsmol/L (P≤0.05). Experiment 2 tested the semen and distilled water dilutions to perform the HOST (1:5, 1:10, 1:15, 1:20 and 1:25). The 1:15 distilled water HOST was superior when compared to the other protocols (P≤0.05), and was similar to the 1:25 dilution protocol (P≥0.05). The effect of the saline-formol fixation was studied in experiment 3. The semen:distilled water dilution rate used was 1:15. After water bath incubation the sperm were immediately assessed or fixed for later analysis. There were no differences (P≥0.05) in the comparison between the fixed and non fixed protocol. The most efficient HOST to determine the percentage of functional integrity of cryopreserved equine sperm is carried out with 1:15 water distilled dilution (semen:distilled water), incubated for 10 minutes, fixed in saline-formol solution; the immediate reading is not necessary